Spectral response of nitrogen (N) fertilised mature oil palm (Elaeis guineensis) and its relationships to cell morphologies - Ahmad Tarmizi, Wafi (2018)
Nitrogen (N) is uptake by oil palm (Elaeis guineensis) depends on a few factors including palm age. N is consumed in every plant parts but most importantly it is used in the synthesis of chlorophylls. Chlorophyll is often used to determine plant N status in non-destructive sampling. Oil palm physiological responses to N treatment are well studied but the spectral response associated with it is poorly understood. It is suspected that the basis of the spectral response in relation to N comes from the oil palm cell morphologies. Opportunities has presented itself to study the effects of N treatment on the cell morphologies and to link this to the spectral response obtained through multiple sensors such as SPAD and spectroradiometer. Two experimental sites belonging to United Melaka Berhad Plantation with oil palm age 12 and age 15 were chosen. Each site was randomly divided into split plot of N treatment. The treatment was 0 kg, 1 kg, 2 kg of N. leaf cell structure and spectral data (SPAD and reflectance) from frond 9 and 17 of the oil palm was collected and analysed. The same frond was also subject to histological procedure and 10μm slides was analysed and correlated to spectral data. It was found that cell density played indirect but an important role in partially explaining the spectral readings. Cell density was influenced by both N treatment and palm age. Increasing N treatment increased cell hyperplasic but this may not have direct effect on spectral readings, rather spectral readings was indirectly effected by cell density by the amount of cell that received light directly. The region of 700 – 1350nm have good correlation for chlorophyll prediction. Cell density however, have weak correlation with any wavelength with the r value ranging from r= - 0.6 to 0.2.